Ascidians (Tunicata) of the French Guiana Expedition - Monniot, Françoise (Zootaxa, 2016)
Ascidians were collected along the shore of Iles du Salut and deeper on the slope in a program of evaluation of the biodiversity in Guiana. Most of the samples belong to already known species from the Caribbean area and Brazilian coast. The colonial forms dominate. The 6 new species have been dredged deeper than 50m but not found by SCUBA divers. In spite of an intensive sampling, the ascidian diversity in Guiana is low with 36 species recorded. This is the result of the abundance of sediment suspended in the water and uniformly deposited on all substrates which affects filtration rate and limits the settling of the ascidian larvae.